2004
DOI: 10.1002/mds.20190
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of individual finger movements in patients with hand dystonia

Abstract: We investigated finger movements in patients with hand dystonia to compare the kinematics of repetitive individual and non-individual finger oppositions. We used an optoelectronic motion analysis system to record movements in 3-D space, and recorded three 5-second trials for each task, counting how many finger oppositions subjects carried out during each trial, and measured the duration and amplitude of flexions, extensions, and pauses. During tasks, normal subjects and patients carried out finger flexions fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Specifically, one suggested mechanism, found in several studies of FTSD patients, is the development of impaired surround inhibition, a neural inhibitory mechanism responsible for the selective recruitment and activation of muscles necessary for a particular task with inactivation of the neighboring muscles that are unnecessary [27, 29, 30]. Consistent with the hypothesis of decreased SICI and impaired surround inhibition, multiple studies have shown a loss of dexterity and impaired independent movement of fingers of patients with either writer’s cramp or musician’s dystonia [3133]. …”
Section: Advances In Understandingmentioning
confidence: 99%
“…Specifically, one suggested mechanism, found in several studies of FTSD patients, is the development of impaired surround inhibition, a neural inhibitory mechanism responsible for the selective recruitment and activation of muscles necessary for a particular task with inactivation of the neighboring muscles that are unnecessary [27, 29, 30]. Consistent with the hypothesis of decreased SICI and impaired surround inhibition, multiple studies have shown a loss of dexterity and impaired independent movement of fingers of patients with either writer’s cramp or musician’s dystonia [3133]. …”
Section: Advances In Understandingmentioning
confidence: 99%
“…Patients with writer's cramp (WC) exhibit movement slowness (Curra et al . ), inaccurate force control (Nowak et al . ) and impaired behavioural response inhibition (Stinear & Byblow, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous behavioural studies have characterized impairments of hand motor dexterity due to FTSD. Patients with writer's cramp (WC) exhibit movement slowness (Curra et al 2004), inaccurate force control (Nowak et al 2005) and impaired behavioural response inhibition (Stinear & Byblow, 2004a). Musician's dystonia (MD) disrupts timing control of sequential and individuated finger movements (Jabusch et al 2004;Furuya & Altenmüller, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, rhythmic variability of sequential and individuated finger movements was pronounced in musicians with FD 45 46 . Patients with writer’s cramp displayed slower finger movements during repetitive and individuated finger oppositions 47 , more variable peak velocity of the hand during circle drawing 48 , and less accurate control of grip force 8 11 . These studies identified abnormalities of the spatiotemporal features of movements in FD patients.…”
mentioning
confidence: 99%